A Method to Control the Transverse Corner Cracks on a Continuous Casting Slab by Combining Microstructure Analysis with Numerical Simulation of the Slab Temperature Field. Issue 5 (6th March 2018) - Yang, Xiaogang; Zhang, Lifeng; Lai, Chaobin; Li, Shusen; Li, Ming; Deng, Zhihao
Abstract : In the current article, a method based on analysis of the microstructure combined with numerical simulation of the temperature field of a continuous casting slab is proposed to eliminate the transverse cracks occurred in slab corners. The microstructures near the cracks will be varied as the phase‐transformation conditions change. Thus, the cracking temperature range can be effectively estimated by analyzing the microstructures near the cracks. The different behaviors of microstructures near cracks in three conditions are presented and discussed. These behaviors include the following: the decarburization layer is symmetrically distributed on both sides of the cracks; the microstructures are refined near the cracks; the cracks "open" the ferrite along the austenite grain boundaries, which results in the ferrite being symmetrically distributed on both sides of the cracks. The variation of the slab corner temperature during a continuous casting process is calculated and discussed. Then, a secondary cooling adjustment scheme is proposed to eliminate the occurrence of transverse corner cracks on the slab surface. Results from industrial practice show that the method can effectively avoid the generation of slab surface cracks without damage to the internal quality of the slab. The method can also be applied to other studies of crack control. Abstract : A method, that is, based on the microstructure analysis combined with numerical simulation of the temperature field of continuous casting slab is proposed to control the transverse corner cracks on slabs. It provides a new idea for the control of transverse corner cracks. The industrial practice results show that the method can effectively control the occurrence of the cracks.